Barriers to and Suggestions for a Healthful, Active Lifestyle as Perceived by Rural and Urban Costa Rican Adolescents - Monge-Rojas, Rafael (2009)
An inactive lifestyle is considered one of the leading causes of obesity and other chronic diseases.1 An active lifestyle, in contrast, is a broad concept that incorporates exercise, recreational activities, household and occupational activities, and active transportation.2 Although establishing an active lifestyle early in life may promote improved health and quality of life in adulthood,3 several studies have shown that physical activity starts declining early in the adolescent years4,5 and continues to decline throughout the life span.6,7 This study aims to expand knowledge of what barriers and motivators may contribute to this decline in physical activity, particularly in the adolescent years. There is a critical need for understanding the factors related to the adoption of a healthful, active lifestyle in the adolescent population. This issue has remarkable importance in Latin America, where the adolescent population (10-19 years of age) represents a significant proportion of the general population (on average 21%), and where very little is known about barriers and motivators to an active lifestyle. Specifically, in Costa Rica more than 50% of adolescents have been found to be at risk of inactive lifestyles, as defined by low cardiovascular fitness.8 The prevalence of overweight, obesity, and chronic diseases in many Latin American countries represents an unprecedented public health challenge that must be addressed from the prevention standpoint.9 Developing strategies to encourage an active lifestyle among adolescents may contribute to reducing the prevalence of chronic disease in these countries. This study assessed the perceptions of rural and urban Costa Rican adolescents regarding which factors affect their adoption of a healthful, active lifestyle and explores their suggestions to encourage the adoption of such a lifestyle